The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/2515-7620/ab4eba
|View full text |Cite
|
Sign up to set email alerts
|

Lime movement through highly weathered soil profiles

Abstract: Applying lime is a fundamental practice for abating acidity in highly weathered soil, but better management strategies for no-till systems are needed to prevent surface pH elevation with little to no subsurface effects. This study was conducted to quantify chemical changes within the soil profile in response to lime and straw applications under both greenhouse and field conditions. Four controlled environment experiments (soil columns) and one field study were conducted on soils classified as Rhodic Hapludox a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(44 reference statements)
2
10
0
Order By: Relevance
“…As a result, aluminum concentration was only high in the B1 horizon of the non-incorporated pots, where pH remained consistently low (Table 1). These results supports the findings of Nunes et al (2019) that incorporation is required to change soil pH at depth. Australian soils can be highly acidic to depths of 40 to 100 cm, naturally or due to agronomic practices (Isbell 2016).…”
Section: Lime and Soil Incorporation In Controlled Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, aluminum concentration was only high in the B1 horizon of the non-incorporated pots, where pH remained consistently low (Table 1). These results supports the findings of Nunes et al (2019) that incorporation is required to change soil pH at depth. Australian soils can be highly acidic to depths of 40 to 100 cm, naturally or due to agronomic practices (Isbell 2016).…”
Section: Lime and Soil Incorporation In Controlled Conditionssupporting
confidence: 91%
“…An international review of liming experiments indicated that the application method of lime (surface, plow, subsoiling) did not affect the change in soil pH achieved through liming, although the review did not specifically consider varying soil depths (Li et al 2019). Rainfall can be low in Australian agricultural areas, and both field and pot studies indicate that in weathered soils, lime will not move farther than 2.5 cm through the soil profile without incorporation (Nunes et al 2019). Lime incorporation through cultivation will bury weed seed, changing the emergence patterns of the weed in subsequent seasons (Chauhan et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…With more-precise sampling from the soil pit face, the increase in soil pH in our study was restricted to the top 0.15 m depth ( Fig. 2e and f), similar to that measured by Nunes et al (2019). Unlimed control plots were acidified at all sampling depths at 0.010 pH units per year.…”
Section: Restricted Vertical Movement Of Alkali In Long-term Lime Expsupporting
confidence: 82%
“…There was no evidence of increasing soil solution pH below 0.20 m depth, contrary to the evidence reported by Whitten (2002) in which a much higher watering regime was applied compared with our experiment. Our experiment suggests that the potential to treat subsurface soil acidity by surface incorporation of high rates (3-6 Mg ha -1 ) of lime is limited and likely only to be effective in less-acidic topsoil (pH > 5) in higher rainfall regions, but the rate of improvement in pH is slow as measured by Nunes et al (2019), and slower than that measured by Whitten (2002). This prompted us to test whether strategic deep tillage is a better solution for deep incorporation of lime for rapid amelioration of subsurface soil acidity.…”
Section: Factors Affecting Vertical Movement Of Alkali In Soil Columnsmentioning
confidence: 54%
See 1 more Smart Citation